Bentuk Optimalisasi Guru Penggerak di Sekolah Dasar Negeri 3 Sadeng - Asep Purwo Yudi Utomo; Ngabiyanto Ngabiyanto; Isnarto Isnarto; Didi Pramono; Arka Yanitama; Galih Suci Pratama (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
This article discusses the "Empowering Pioneer Teachers" program implemented at Public Elementary School 3 Sadeng, aiming to enhance the quality of education and nurture holistic student development. The program is rooted in education that embraces diversity and adapts to changing times. Pioneer teachers are selected based on their enthusiasm, dedication, adaptability, in addition to academic qualifications. The article reviews the stages of selection, intensive training, and program implementation within classrooms. The program emphasizes the development of interpersonal competencies and innovation in teaching methodologies. Support from the school, parents, and local community plays a crucial role in the program's success. Its impact is evident in improved student learning outcomes, social skills, creativity, and the cultivation of an inclusive and collaborative learning environment. Through this article, it is hoped that the experience of Public Elementary School 3 Sadeng can inspire other educational institutions. Empowering pioneer teachers yields positive effects throughout the school community and has the potential to guide elementary education towards a brighter and more equitable future.